THE ROLE OF LANGUAGE PROFICIENCY AND BIOGRAPHIC FACTORS IN PREDICTING TEACHER SELF-EFFICACY: EVIDENCE FROM JAPANESE EFL TEACHERS - OGATA, KENSAKU (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study investigated how perceived English language proficiency and biographic factors predict teacher self-efficacy among Japanese EFL teachers. Quantitative data were collected from 132 in-service teachers through a survey incorporating the Teachers’ Sense of Efficacy Scale and a self-assessment of language proficiency. Regression analyses revealed that perceived language proficiency was the strongest predictor of teacher self-efficacy (r = .492, p < .001), followed by teaching experience (r = .328, p < .001). Education level showed only a small correlation (r = .141, p = .012) and was not significant in the regression model, while overseas experience exhibited no effect (p = .850). These results highlight the pivotal role of communicative competence and sustained teaching experience in enhancing teachers’ confidence and instructional effectiveness. The findings suggest that teacher education and professional development programs should move beyond credential-based evaluation to emphasize competence-oriented training and continuous language development. Such efforts may foster a more empowering environment for teacher growth, resilience, and long-term retention within Japan’s EFL context.